PERANCANGAN SISTEM INVENTORY BARANG LABORATORIUM TJKT BERBASIS WEB DI SMK DIPONEGORO BANYUPUTIH - Hanif, Syahrul; Widayati, Yohana Tri; Prakoso, Satrio Agung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to design a web-based TJKT laboratory inventory system at SMK Diponegoro Banyutputih. This system is designed to overcome the problem of manual inventory management, which often causes data inaccuracy and low efficiency. This system uses Laravel framework for web development and MySQL database for data storage. The main features developed include recording incoming and outgoing goods, stock tracking, and generating inventory reports. System testing shows that this system is able to improve the accuracy of inventory data and simplify the process of managing goods in the laboratory. With the implementation of this system, it is expected to achieve operational efficiency and better inventory management in the TJKT laboratory of SMK Diponegoro Banyutputih.